Optimum concentration of dissolved oxygen for the survival of virulent Treponema pallidum under conditions of low oxidation-reduction potential. - Graves, S (1979)
A maintenance medium with a low oxidation-reduction (redox) potential, when gently bubbled with 5% oxygen in nitrogen or with air for various periods of time, gave a range of dissolved oxygen concentrations between 1.6 and 5.8 micrograms/l. Virulent Treponema pallidum (Nichols strain) inoculated into these media were assayed 24 and 48 hours later for motility and virulence and were compared with samples taken at zero time. Virulent T. pallidum survived best in the presence of 2.4 micrograms/l dissolved oxygen over a 48-hour period, which corresponded to a gaseous mixture of 3% oxygen in nitrogen. Higher concentrations of oxygen did not give significantly different results from anaerobic conditions over this period. Thus, until it can be grown in vitro, T. pallidum would appear to be a microaerophilic bacterium.